Intensification of insulin treatment with insulin degludec/Aspart in type 2 diabetic patients: A 2-year real-world experience - YAVUZ, DİLEK (My University, 2022)
Aim: To evaluate the effects of insulin degludec/insulin aspart (IDegAsp) coformulation as an intensification of insulin treatment for glycemic control in patients with type 2 diabetes (T2D) in a long term real-world clinical setting. Materials and Methods: This retrospective non-interventional study, included 210 patients with T2D who to IDegAsp coformulation from prior insulin treatment in a tertiary endocrinology center between September 2017 and December 2019. The baseline data was taken as the index date and defined as the first IDegAsp prescription claim. Previous insulin treatment modalities, hemoglobin A1c (HbA1c), fasting plasma glucose (FPG), and body weight were recorded, respectively at the 3rd, 6th, 12th, and 24th months of the IDegAsp treatment. Results: Out of the total 210 patients, 166 patients under insulin treatment switched to twice-daily IDegAsp treatment, 35 patients switched to once daily IDegAsp and twice premeal short-acting insulin regimen as a modified basal-bolus (BB) treatment, and nine patients commenced with once-daily IDegAsp treatment. HbA1c decreased from 9.2% ± 1.9% to 8.2% ± 1.6% in 6 months, 8.2% ± 1.7% in the first year, and 8.1% ± 1.6% in the second year of the therapy (p< 0.001). FPG decreased from 209.0 ± 85.0 mg/dL to 147.0 ± 62.6 mg/dL in the second year (p< 0.001). The required total daily dose of insulin increased in the second year of IDegAsp treatment compared to baseline. However, there was a borderline significance increase in IDegAsp requirement for the whole group at the two-year follow-up (p = 0.05). Patients who were administered twice daily IDegAsp injections required more total insulin in the first and second years due to added premeal short-acting insulin injections (p < 0.05). The frequency of patients with HbA1c < 7% was 31.8% in first year and 35.8% in second year under IDegAsp treatment.Insulin dose was de-escalated in 28.5% of the patients under BB treatment, while 15% under twice-daily IDegAsp required increased BB treatment. Conclusion: Intensification of insulin treatment with IDegAsp coformulation improved glycemic control in patients with T2D. The total daily insulin requirement increased but the IDegAsp requirement lightly increased at the two-year follow-up. Patients under BB treatment required de-escalation of insulin treatment.
Keywords: : IDegAsp1; insulin2; degludec3; real world4; type 2 diabetes5; intensification6